A longitudinal study of language learners’ images about Russia - Nikitina, L. (2016)
Several studies in the field of applied linguistics have explored images held by language learners about a target language country. However, for the most part, these studies focused on learners of modern European languages, such as German, Spanish and French and they were conducted in Western educational contexts. Besides, none of the previous investigations attempted to conduct a systematic classification of the language learners’ images. The present longitudinal study addressed these gaps in the research literature. It explored images about Russia held by Malaysian learners of the Russian language in a large university in East Malaysia. This article reports the findings of three questionnaire surveys conducted in 2004, 2007 and 2010. It was found that the images about Russia held by the participants were diverse and clustered around eight country related aspects. Content of some categories of images was stable and changed little over time. Other categories were more fluid and more prone to change. The paper concludes with a discussion of pedagogical implications that can be derived from the findings.